Financial distress and earnings management: The role of audit quality - Amelia Oktrivina (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2022)
This research was aimed to examine the effect of financial distress on earnings management, moderated by audit quality in manufacturing companies listed on the Indonesian stock exchange 2017 – 2020. The type of data in this study is secondary data with a sample selection method that is purposive sampling method. The analysis model used is panel data, regression analysis and data processing using Eviews12. The sample in this research is 83 manufacturing companies for the 2017-2020 research year. The results of this study indicate that the financial distress variable has a significant negative effect on earnings management and audit quality variable weakens financial distress on earnings management.